Transformasi UMKM Menuju Ekonomi Digital: Implementasi QRIS di Desa Batu Belah oleh Mahasiswa KKN MBKM FH UNRI dalam Bingkai Regulasi Hukum Sistem Pembayaran - Musliadi, Ricki; Markalino, Yuandha; Tambunan, Daniel Joenathan; Susanti, Meri Yulia; Napitupulu, Christin Amelia Carolina; Panggabean, Muhammad Novan Anugerah; Sihombing, Kristesya Veronika Br.; Septhia, Ayu; Aurelia, Fidela Nur; Simanjuntak, Daniel Novaldo Haposan; Putri, Marsya Awalia (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2025)
The 2025 Community Service Program (Kuliah Kerja Nyata - KUKERTA) of the Merdeka Belajar - Kampus Merdeka (MBKM) at Universitas Riau is an implementation of the Three Pillars of Higher Education, specifically community service. The 2025 UNRI KUKERTA Program serves as a platform for students to learn and contribute simultaneously, absorbing real-world societal issues, and applying knowledge through tangible community empowerment to generate programs that are feasible, acceptable, participatory, and sustainable. Batu Belah Village, Kampar District, Kampar Regency, possesses MSMEs (Micro, Small, and Medium Enterprises) with significant potential for development, yet their operations remain largely confined to conventional cash-based transactions. Low digital literacy, limited understanding of legal regulations, and inadequate supporting facilities hinder the adoption of QRIS-based digital payment systems. Through the KKN program, students implemented a participatory and educational approach encompassing socialization, technical training, direct mentoring, and monitoring and evaluation to enhance MSMEs' practical understanding and capability in utilizing QRIS. As a result, MSME actors in Batu Belah Village successfully created QRIS accounts independently, understood digital transaction mechanisms, and began integrating non-cash payments into their business operations. The conclusion of this activity indicates that student-led, community-based mentoring not only accelerates the adoption of digital payment technology but also strengthens the foundation for transforming the MSME economy towards an inclusive and sustainable digital ecosystem, supported by a clear legal-regulatory framework.